(3TQM GdQSGdI GdYVOjI aj GdhVYs - (3GdSeQbfOj, CHh GdbGSe Hf CHj HcQ, cGf MjG (B888(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj NU GdEfSGf HeYQaI ChVGY GdcdGehHYO adeG TGY aj GdCeUGQ hXgQ XghQ GdTeS aj GdfgGQ GdYVOjICQOJ GdNhV aj JJeje gPG GdeQGes
(3BNQgG (B:s
(3fGbU GdBNQ hBNQg(B: (3afbhd Cf GdeYGfj bO Jchf edMhXI bUOG hHGdPGJ hbO Jchf edMhXI JHYG ZjQ ebUhOI HPhGJgG Hds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 173s
(3eYLe GdeDdajf(B: 2 / 643s
(3cTa GdXfhf(B: 1 / 898s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GddZIs